The Role of Product Innovation in Mediating the Entrepreneurial Competence and Motivation on the Performance of Packaged Food MSMEs - Anis Mid Roroh; Siti Haerani; Fauziah Umar (Hasanuddin Journal of Business Strategy, 2021)
This study aims to analyze the influence of entrepreneurial competence and entrepreneurial motivation on the performance of packaged food MSME actors through the innovative products in Mamuju Regency. This research was conducted using quantitative data, while the data collection techniques were observation, questionnaires, and interviews. The sampling technique used in this study was sampling with a saturated sampling method where the researcher used all members of the population totaling 70 business actors. Data testing is done by using validity, reliability, and hypothesis testing. The data obtained were analyzed by descriptive analysis and path analysis. The results showed that entrepreneurial competence and entrepreneurial motivation had a positive and significant effect on innovative products. Entrepreneurial competence, entrepreneurial motivation, and innovation products had a positive and significant effect on the performance of packaged food MSME. Entrepreneurial competence and entrepreneurial motivation through innovation products have an indirect effect on the performance of packaged food MSME actors in Mamuju Regency.